EFL Curriculum Reform in Indonesia: From KTSP to Kurikulum 2013 to Kurikulum Merdeka - Karimah, Laisa; Syafa'ah, Lailis; Angraini, Nuriska Julia; Hasibuan, Kalayo (JELT: Journal of English Language Teaching, 2026)
This article examines the trajectory of EFL curriculum reform in Indonesia from the decentralized KTSP model through the competency-based Kurikulum 2013 to the recent, more flexible Kurikulum Merdeka, highlighting shifts in curriculum aims, assessment practices, teacher roles, and classroom implementation; it synthesizes empirical and policy literature that reports a move from locally adaptable syllabuses (KTSP) to nationally standardized competency frameworks (Kurikulum 2013) and then toward learner-centered autonomy and contextualization under Kurikulum Merdeka, identifies persistent challenges including uneven teacher readiness, infrastructure and resource gaps, and assessment misalignment, and recommends sustained teacher professional development, clearer assessment-design alignment, and stakeholder engagement to ensure intended EFL learning outcomes.